DATA PROCESSING APPLICATIONS TITHE USING MICROSOFT VISUAL BASIC 6.0 - Rani Sutarbin; Rahayu Noveandini, SKom, MM (Jurnal Sistem Informasi, 2005)
In the holy month of Ramadan there is a mandatory worship should be done by Muslims, one of them is performing tithe. Dsyariatkan tithe as the end of Ramadan, aims to rid themselves of the things that littered the fast and compensation for those needy and poor. In the process of tithe payments are collecting zakat committee consisting of the Amil Zakat, Amil trusted to receive and collect all the alms that have been paid by the giver of zakat (Muzaki), and distribute to the recipient entitled to zakat (Mustahiq). But in its implementation in the field, the Zakat is still confronted by various difficulties one of them is in data processing because it is still a lot of Zakat Zakat committees who use the manual way of bookkeeping so that in the process of making reports, they will have trouble if the amount of data collected already achieve maximum intensity of the abilities of Zakat is required a high level of accuracy in data processing in order to produce good and accurate information.